1987
DOI: 10.3181/00379727-184-42486
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Glucagon Receptors and Metabolic Profile in Two Strains of Rats: Wistar-Furth and Sprague-Dawley

Abstract: We studied glucagon and insulin binding to isolated hepatocyte receptors in Wistar-Furth (WF) and Sprague-Dawley (SD) rats, using '251-labeled hormones. Hepatocytes from WF rats bound more glucagon than hepatocytes from SD rats. There were no differences in insulin binding. These observations prompted us to investigate other strain differences. Fasting and nonfasting serum glucose, glucagon, insulin, and growth hormone were measured. WF animals had a lower fasting glucose and higher fasting glucagon than SD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…This agrees with the previous report, which showed significant changes only after 4 days culture with growth hormone [12]. Hepatocytes from Wistar rats Previous studies have indicated that there are differences in the plasma concentrations of glucose, insulin, glucagon and possibly also growth hormone, and differences in glucagon receptors, between the Sprague-Dawley and Wistar strains of rats [25]. Experiments were carried out with hepatocytes from normal Wistar rats (Table 3) under similar conditions to those used above for Sprague-Dawley rats (Tables 1 and 2).…”
Section: Nadp-linked Dehydrogenases In Hepatocytes From Sprague-dawlesupporting
confidence: 93%
See 2 more Smart Citations
“…This agrees with the previous report, which showed significant changes only after 4 days culture with growth hormone [12]. Hepatocytes from Wistar rats Previous studies have indicated that there are differences in the plasma concentrations of glucose, insulin, glucagon and possibly also growth hormone, and differences in glucagon receptors, between the Sprague-Dawley and Wistar strains of rats [25]. Experiments were carried out with hepatocytes from normal Wistar rats (Table 3) under similar conditions to those used above for Sprague-Dawley rats (Tables 1 and 2).…”
Section: Nadp-linked Dehydrogenases In Hepatocytes From Sprague-dawlesupporting
confidence: 93%
“…It has been shown that a single injection of growth hormone causes acute down-regulation of hepatic growthhormone receptors in hypophysectomized rats [34]. The variability in the effects of growth hormone in hepatocytes from Wistar rats may be related to the variability in plasma growth-hormone concentration in this strain of rats [25].…”
Section: Sprague-dawley and Wistar Ratsmentioning
confidence: 99%
See 1 more Smart Citation